Interaksi antara Perubahan Sosial dan Hukum Keluarga Islam: Sebuah Studi Kasus tentang Peran Perempuan dalam Pengambilan Keputusan Keluarga - Ashari, Beni (UAS PRESS, 2024)
Family dynamics, including decision-making, are greatly impacted by dynamic social developments. The purpose of this study is to examine how Islamic family law and social change interact, with an emphasis on how women participate in family decision-making. This study uses in-depth case studies to investigate the ways in which Islamic family law concepts intersect with social changes including modernization, urbanization, and the rise in women's education. This study uses case study techniques in conjunction with a qualitative approach. In-depth interviews with women of all ages and socioeconomic backgrounds were used to gather data, and pertinent Islamic law materials were also examined. The findings of the study show that women's roles in family decision-making have changed significantly. Despite the fact that Islamic law has always given men more authority as heads of